Tobacco Taxation Incidence : Evidence From Russia - Fuchs, Alan; Matytsin, Mikhail; Obukhova, Olga (World Bank, Washington, DC, 2018)
The results in this report for the Russian Federation support the use of tobacco taxation as an effective means to reduce tobacco consumption, raise government revenues, increase public health and promote income equality.